Enhancing cell migration in shape-memory alginate–collagen composite scaffolds: In vitro and ex vivo assessment for intervertebral disc repair. (April 2015) - Guillaume, Olivier; Naqvi, Syeda Masooma; Lennon, Kerri; Buckley, Conor Timothy
Lower lumbar disc disorders pose a significant problem in an aging society with substantial socioeconomic consequences. Both inner tissue (nucleus pulposus) and outer tissue (annulus fibrosus) of the intervertebral disc are affected by such debilitating disorders and can lead to disc herniation and lower back pain. In this study, we developed an alginate–collagen composite porous scaffold with shape-memory properties to fill defects occurring in annulus fibrosus tissue of degenerated intervertebral discs, which has the potential to be administered using minimal invasive surgery. In the first part of this work, we assessed how collagen incorporation on preformed alginate scaffolds influences the physical properties of the final composite scaffold. We also evaluated the ability of annulus fibrosus cells to attach, migrate, and proliferate on the composite alginate–collagen scaffolds compared to control scaffolds (alginate only). In vitro experiments, performed in intervertebral disc-like microenvironmental conditions (low glucose and low oxygen concentrations), revealed that for alginate only scaffolds, annulus fibrosus cells agglomerated in clusters with limited infiltration and migration capacity. In comparison, for alginate–collagen scaffolds, annulus fibrosus cells readily attached and colonized constructs, while preserving their typical fibroblastic-like cell morphology with spreading behavior and intense cytoskeleton expression. In a second part of this study, we investigated the effects of alginate–collagen scaffold when seeded with bone marrow derived mesenchymal stem cells. In vitro, we observed that alginate–collagen porous scaffolds supported cell proliferation and extracellular matrix deposition (collagen type I), with secretion amplified by the local release of transforming growth factor-β3. In addition, when cultured in ex vivo organ defect model, alginate–collagen scaffolds maintained viability of transplanted mesenchymal stem cells for up to 5 weeks. Taken together, these findings illustrate the advantages of incorporating collagen as a means to enhance cell migration and proliferation in porous scaffolds which could be used to augment tissue repair strategies.